Analisis sedimentasi terhadap umur guna Bendungan Ponre-Ponre - Salmiah, Endi Haskaer Hafid; Musa, Ratna; Mallombasi, Ali (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
The research involves collecting historical sedimentation data, analyzing sediment distribution, and calculating the actual capacity of the reservoir. The average annual sedimentation was recorded at 0.597 million m³, this value is five times greater than the initial prediction of 0.1 million m³ per year. The measurement results show that the reservoir storage capacity in 2023 will be 33.81 million m³, a decrease from the initial capacity of 40.4 million m³. The high rate of sedimentation is caused by factors such as changes in land use in the upstream watershed, high rainfall in the area, and soil erosion due to human activities. The impact is a significant reduction in reservoir storage capacity, reducing its useful life from initial planning to around 15 years faster. The distribution of sedimentation in the Ponre-Ponre Dam shows diverse patterns, including delta deposits in the upstream section, tapering deposits in the middle zone, and wedge-shaped deposits around the dam. This pattern reflects the distribution of coarse material which is concentrated in the upstream area, while fine material tends to settle in the downstream area. In addition, the data shows an increase in the elevation of the reservoir base due to sediment accumulation which reaches an average of 7.6 mm per year. The conclusion of this research is that sedimentation has reduced the effective capacity of the storage, thereby accelerating the reduction in the useful life of the dam. To overcome this problem, it is recommended to implement intensive land conservation in the upstream watershed, optimize reservoir operations through flushing and dredging methods, and develop a technology-based monitoring system to extend the useful life of the dam. Apart from that, collaboration between the government and the community in maintaining the upstream watershed ecosystem is the key to sustainable management of the Ponre-Ponre Dam.